The relationship of physical activity, dietary patterns, and energy intake with overweight incidence among Sabhara members at Langkat police station - Alhafiz, Muhammad Daffa; Lubis, Halinda Sari (TROPHICO, 2025)
Occupational Safety and Health (OSH) is an effort to ensure the physical and mental well-being of workers, which is essential for productivity. Health and work ability are closely related to nutritional status, where balanced calorie intake supports energy and effective task performance. Conversely, being overweight or obese increases the risk of degenerative diseases and is influenced by multifactorial causes such as genetics, lifestyle, and poor diet. This study aimed to examine the relationship between physical activity, dietary patterns, and energy intake with overweight among SABHARA members at the Langkat Police Headquarters as an important basis for health interventions. This study employed an analytical quantitative method with a cross-sectional design. The sample was obtained through simple random sampling, consisting of 49 members. The data collected included nutritional status (body scale, micrometer), energy intake (24-hour food recall), dietary patterns (FFQ), and physical activity (IPAQ Short-Form). The data were analysed using the Chi-Square test. The results showed that 57.1% of members were overweight, 18.3% had low physical activity, 53.1% had poor energy intake, and 49.0% had inadequate dietary patterns. The findings showed a significant relationship between physical activity, dietary patterns, and energy intake with overweight.